Pigmented demodicidosis ‐ an under‐recognized cause of facial hyperpigmentation. (13th December 2021) - Feuerman, Hana; Atzmony, Lihi; Glick, Mirit; Sherman, Shany; Snast, Igor; Hodak, Emmilia; Segal, Rina
Abstract: Background: There is a paucity of data regarding demodicidosis‐associated facial hyperpigmentation. Objective: To delineate the clinical, dermoscopic, and histopathologic features of demodicidosis‐associated facial hyperpigmentation. Methods: Clinical and diagnostic data were collected from the medical files of patients who were referred to our outpatient dermatology clinic in 2006–2019 for evaluation of facial hyperpigmentation and were diagnosed with demodicidosis. Results: The cohort included 19 patients (13 male) aged 42–76 years, all with Fitzpatrick skin type 3–4. All presented with mostly asymptomatic dusky, brown‐gray, facial pigmentation, localized or diffuse with background erythema in 36.8% of cases, and skin roughness in 26.3%. Dermoscopy yielded characteristic findings of white gelatinous or opaque protrusions from hair follicles or infiltration of follicular openings with an amorphic material. A specific finding was perifollicular and reticulated pigmentation of the affected areas. Findings were confirmed on microscopic ( n = 7) and histopathologic ( n = 5) studies. Anti‐demodectic treatment led to complete (73.6%) or partial (23.4%) resolution of pigmentation within 2 years. Conclusion: We describe unique clinicopathological and dermoscopic findings associated with an under‐recognized type of facial hyperpigmentation caused by demodex for which we propose the term "pigmented demodicidosis." Demodicidosis should be added to the list of causes of facial hyperpigmentation.